2012
DOI: 10.1038/sc.2012.124
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injuries as a consequence of falls: are there differential rehabilitation outcomes?

Abstract: Study design: Case series, consecutive sample, survey. Objectives: To examine the incidence of spinal cord injuries sustained as a result of falls compared with other causes, and to investigate rehabilitation outcomes between these two groups. Settings: Tertiary care, spinal cord injury rehabilitation unit (National Spinal Injuries Center), Stoke Mandeville Hospital, UK. Methods: Demographic information and descriptive statistics were examined for individuals sustaining their injury via falls vs non-falls. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…23 A slightly higher percentage of whites were observed in our fall group compared with the non-fall group. However, because these are proportions rather than incidence rates, one cannot draw a conclusion that whites fall more often than non-whites.…”
Section: Fall Vs Non-fall Etiologiesmentioning
confidence: 83%
“…23 A slightly higher percentage of whites were observed in our fall group compared with the non-fall group. However, because these are proportions rather than incidence rates, one cannot draw a conclusion that whites fall more often than non-whites.…”
Section: Fall Vs Non-fall Etiologiesmentioning
confidence: 83%
“…Possible explanations for the functional outcome differences between the age groups is that the prevalence of medical comorbidities prior to TSCI is higher among the elderly and they also suffer from more frequent in-hospital secondary complications [ 27 , 28 ]. Furthermore, prior studies show that patients with older age and those acquiring TSCI as a result of a fall seem to benefit from rehabilitation but achieve less independence in some areas, like mobility, bowel and bladder management compared to patients in the younger age group and patients injured due to other etiologies [ 29 ]. With these results in mind, it is especially profitable to invest in the rehabilitation of working age patients and to prevent falls in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly one percent of the study sample had spinal cord injuries, agreeing with the Oxley et al study [21]. However, it disagrees with the Kennedy et al study reporting nearly a quarter percent of falls had spinal cord injury which may be attributed to the long duration of the study and differences in the heights of fall [22]. More than half of the sample has a major degree of severity which disagreed with Luzia et al, which reported that most injuries were classified as mild.…”
Section: Methods Resultsmentioning
confidence: 62%